Potential roles of export orientation of Cambodia's agriculture and agro-industry: An application of CGE analysis - Sryneath Chhuor (Journal of Economic Structures, 2017)
For a more diversified export structure and a better distribution of domestic income in Cambodia, agriculture and agro-industry have been specified as export potentials. While empirical impact studies within those sectors have been limited, this paper attempts to assess the impacts of the promising export sectors on domestic economy by applying a computable general equilibrium framework. Results show that the increase in export demand for the selected sectors-food-beverage-tobacco, rubber industry, and agriculture-generate favorably on growth, employment, and household welfare, with the contributions of the former two higher than that of the latter, suggesting that priority should be given to agro-processing exports to increase production chain. The findings indicate that in order for the trading sectors to expand the benefits, productivity growth of low-skilled and medium-skilled labor is crucial. The influence of the selected sectors would be greater when the demand disturbance is combined with supply-side efficiency measure to promote the export orientation.
Keywords: 330; Export orientation; Potential export sectors; Computable general equilibrium model; External shocks; Productivity